Globalization as a Breakthrough in the Education Field, the Role of the Human Identity in the Contemporary Society - Puka, Edi (Mediterranean Journal of Social Sciences, 2011)
At times, the age of globalization is interpreted as a reproach in respesect to the past of human race, such a radical censurethat everything which was previously believed or done is made irrelevant, thus resulting in an irrelevance of the historical narratives as wellas other forms of memory transmition. Parallelly, it is also accepted as an ineradicale given background of human condition of our daysthe fact that a twist of practices and knowledge, more or less aimed at financial efficiency, has taken the upper hand in the articulated andcomplex cultural identity of our race, to such an extent that it imposes strong constraints to future development of the human knowledge.The image of oneself that every individual tries to affirm in respect to others is inspired on the largest autonomy and personal freedom;identity cultures that modern societies, based on the rights of independence and mutual respect, recognize and contribute to formulate amodern idea of adult age.